1997
DOI: 10.1094/pdis.1997.81.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Improved RNA Extraction from Woody Plants for the Detection of Viral Pathogens by Reverse Transcription-Polymerase Chain Reaction

Abstract: An efficient procedure for the extraction of high-quality RNA from woody plants without the use of phenol, organic solvents, or alcohol precipitation is described. The method employs commercially available spin-column matrices and mitigates the inhibitory effects of plant polysaccharides and polyphenolic compounds commonly observed on subsequent polymerase chain reaction amplification when conventional extraction methods are applied to woody plant species. The method described has been successfully used in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
200
0
7

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(211 citation statements)
references
References 14 publications
1
200
0
7
Order By: Relevance
“…Kinard et al (7) and MacKenzie et al (11) also reported the detection of ASGV, especially from bark and leaves of apple trees, by RT-PCR. Both used total RNA preparations as template in a classical twostep system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kinard et al (7) and MacKenzie et al (11) also reported the detection of ASGV, especially from bark and leaves of apple trees, by RT-PCR. Both used total RNA preparations as template in a classical twostep system.…”
Section: Discussionmentioning
confidence: 99%
“…Serological detection by enzyme-linked immunosorbent assay (ELISA) using commercially available antisera represents the first alternative for biological indexing, but its use is limited to a short time period in the growing season and appears inappropriate with dormant woody tissues (7,8,11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Total RNA was extracted using RNeasy Plant Mini kit (Qiagen, Germany). For DNA extraction CTAB method was used [14,15]. Reverse transcription was carried out in a 25 ll reaction mixture containing 7 ll total RNA (1-1.5 lg), 1.0 ll of 0.2 lg/ll of random hexamer primers, 1.0 ll of 40 mM dNTP mix (Fermentas, Lithuania), 5 ll of 59 RT buffer and 100 Units of M-MuLV Reverse Transcriptase (USB Corporation, USA).…”
mentioning
confidence: 99%